ECONOMIC EMPOWERMENT THROUGH BUYING INTENTION ON ONLINE MARKETING IN INDONESIA - Deden Novan Setiawan Nugraha (Universitas Pasundan, 2019)
Community economic empowerment is an effort to make the economy strong, large, modern and highly competitive in the right market mechanism. The constraints of people's economic development are structural constraints; the empowerment of the people's economy must be carried out through structural change. One of them is structural change through technology by online shopping application. The purpose of this research is to find out how the influence of online marketing variables which consist of Personal Relevance, Online Interactivity, Message, and Brand Familiarity Brand towards buying intention. In this study, researchers took objects on the online shopping application Qlapa.com which specifically sells handmade products. The sampling technique used by researchers is a non-probability sampling technique, because not all samples have criteria which are in accordance with what the researcher determined. Based on the calculations made, the sample used in this study was 100 people. The research method used in this research is quantitative methods. The analysis was conducted using the method of multiple regression analysis to explain the effect of the variables. The problems examined in this study are Personal Relevance (X1), Online Interactivity (X2), Message (X3), Brand Familiarity (X4), and Buying Intention (Y). The results of the study found that simultaneously and partially the variables Personal Relevance, Online Interactivity, Message, and Brand Familiarity have a significant influence on buying intention